PUBLIC-PRIVATE PARTNERSHIP, “TRIPLE HELIX” AND CORPORATE SOCIAL RESPONSIBILITY - V. P. Shestak (Финансы: теория и практика, 2017)
The article offers an updated vision of interaction between business and society in Russia; it argues that the Russia’s current economic crisis is of systemic nature, and numerous international rankings have been asserting this fact. It offers insight into the main problem of modern Russia - the problem of national security - formulated in the new National Security Strategy (2016). “A social action triangle” for big business is considered as a possible solution to this problem. It includes: public-private partnerships (investment projects), “an innovative triple helix” (innovative projects) and corporate social responsibility (social projects carried out in line with the major activities. Realizing, shaping and implementing new business practices in Russia should be accomplished via support of civil society values by infrastructure monopolies. The highest level of philanthropy in CSR format is a turn of the business from charity to social, economic and infrastructure projects, i.e. establishing partnerships that focus on collaboration based on long-term national interests. To back this new trend, the format of socially oriented public- private investment projects is suggested.